Augmented reality system development : from simple to advance - Basori, Ahmad Hoirul (Penerbit UTM, 2008)
Augmented Reality (AR) is an extended version of virtual reality where it gives more impression for real world presence rather than virtual reality (virtual environment). Azuma (1997) stated that AR gives additional information to user until the user is able to see real world which is combined with virtual object. AR also has a characteristic that consist of combining virtual world, real time interaction and 3D registration (Azuma 1997). The example of AR application can be shown in Figure 8.1. In augmented reality applications the quality and position of camera hold an important role to give a realistic presence in virtual environment. Figure 8.1 has shown the proper combination between virtual object and real object. We hardly seen which one the real object and virtual object. Other elements that very essential are texture and model of the virtual 3D object. The 3D object should be more realistic and representing the real object in real world.